VARAdb: a comprehensive variation annotation database for human. Issue Volume 49:Issue D1(2021) (23rd October 2020) - Pan, Qi; Liu, Yue-Juan; Bai, Xue-Feng; Han, Xiao-Le; Jiang, Yong; Ai, Bo; Shi, Shan-Shan; Wang, Fan; Xu, Ming-Cong; Wang, Yue-Zhu; Zhao, Jun; Chen, Jia-Xin; et al.
Abstract: With the study of human diseases and biological processes increasing, a large number of non-coding variants have been identified and facilitated. The rapid accumulation of genetic and epigenomic information has resulted in an urgent need to collect and process data to explore the regulation of non-coding variants. Here, we developed a comprehensive variation annotation database for human (VARAdb, http://www.licpathway.net/VARAdb/ ), which specifically considers non-coding variants. VARAdb provides annotation information for 577, 283, 813 variations and novel variants, prioritizes variations based on scores using nine annotation categories, and supports pathway downstream analysis. Importantly, VARAdb integrates a large amount of genetic and epigenomic data into five annotation sections, which include 'Variation information', 'Regulatory information', 'Related genes', 'Chromatin accessibility' and 'Chromatin interaction'. The detailed annotation information consists of motif changes, risk SNPs, LD SNPs, eQTLs, clinical variant-drug-gene pairs, sequence conservation, somatic mutations, enhancers, super enhancers, promoters, transcription factors, chromatin states, histone modifications, chromatin accessibility regions and chromatin interactions. This database is a user-friendly interface to query, browse and visualize variations and related annotation information. VARAdb is a useful resource for selecting potential functional variations and interpreting their effects on human diseases and biological processes.